Health-related quality of life among patients with advanced cancer: an integrative review - Maria Eliane Moreira Freire; Namie Okino Sawada; Inácia Sátiro Xavier de França; Solange Fátima Geraldo da Costa; Cecília Danielle Bezerra Oliveira (SciELO, 2014)
This integrative literature review aimed to characterize scientific articles on health-related quality of life - HRQoL - among patients with advanced cancer from national and international literature, and summarize those factors evidenced in the literature that contributed to the improvement or worsening of HRQoL among patients with advanced cancer. The search for materials was conducted in the following databases: CINAHL, EMBASE, PubMed, SciELO and LILACS. Among the 21 articles in the sample, 13 showed an improvement of HRQoL among patients with advanced cancer related to the development of physical, emotional and spiritual interventions. In eight studies, we identified predictive symptoms of low HRQoL, such as pain, fatigue, sleep disorders, depression, nutritional changes, and others. The results showed that clinical manifestations, which many times were inherent in cancer, such as factors that can lower patients' HRQoL, while physical, psychological and spiritual benefits resulting from therapeutic interventions may promote its improvement.